Peran Pengenalan Lapangan Persekolahan (PLP) dalam Meningkatkan Kompetensi Calon Pendidik di SMP Swasta Daya Cipta Medan - Kesya Lamuntazor; Cahaya Permata Sari; Namira Fitri Nasution; Suci Dahlya Narpilla (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
The Introduction to Schooling Field Program (PLP) is a key component in preparing prospective educators with the practical skills needed to face challenges in the world of education. This study aims to explore the role of PLP in improving the competence of prospective educators at SMP Swasta Daya Cipta Medan. Through the PLP program, prospective educators are able to apply the theories learned in college in a real context at school, from observing the learning process to participating in extracurricular activities. PLP also provides opportunities for prospective educators to develop pedagogical, professional, and social competencies through direct interaction with teachers, students, and school staff. This research uses a field research approach with a qualitative descriptive design that aims to describe the phenomena that occur. The main informant in this study was the principal, while supporting informants consisted of the vice principal for curriculum, the head of administration, teachers, and school staff. Data were collected through observation, interview, and documentation methods, which were then analyzed using data analysis techniques to review, reduce, draw conclusions, and use triangulation to ensure data validity. This study found that PLP not only enriched students' theoretical knowledge, but also strengthened their skills in managing classes, developing lesson plans, and adapting to various challenges in the field. The PLP program at SMP Daya Cipta Medan contributes significantly in shaping educators who are competent and ready to face the dynamics of the world of education, as well as being able to make a positive contribution to the development of education in Indonesia.